Contribution to anthropogeographic researches of Council Sjenica - Radovanović Svetlana (Glasnik Srpskog Geografskog Društva, 2005)
In this report special attention is dedicated to clan structure of Serbian and Bosnian (Muslim) population drawn by the field research and the result of the Census of 2002. The review of the number of the households by clans and total number of members (in the country + in labor or staying abroad) is given by the settlements that were classified by ethnic homogeneous.